Certain Transformation Formulae for Polybasic Hypergeometric Series. (20th October 2011) - Srivastava, Pankaj; Rudravarapu, Mohan
Abstract : Making use of Bailey's transformation and certain known summations of truncated series, an attempt has been made to establish transformation formulae involving polybasic hypergeometric series.